WEEKLY TRAINING FREQUENCY AS A CORRELATE OF EXECUTIVE FUNCTION IN SPORT SCIENCE STUDENTS - Septian Williyanto; Herman Subarjah; Surdiniaty Ugelta; Akhmad Fajri Widodo; Iftitakhur Rohmah (Universitas Negeri Gorontalo, 2026)
This Pilot study aimed to examine the relationship between weekly training frequency and executive function among sport science students. A correlational, cross-sectional design was employed involving 50 Sport Science students (32 males, 18 females; age M = 19.56, SD = 0.70 years) who were free of neurological disorders and abstained from caffeine for 12 hours prior to testing. Weekly training frequency was self-reported, while executive function was assessed using the Digit Span Test, Stroop Test, and Trail Making Test (TMT). Because several variables were not normally distributed (Shapiro–Wilk test), Spearman's rho correlation was used as the primary analysis, supplemented with Kruskal–Wallis tests across training-frequency categories and Mann–Whitney U tests for sex comparisons. Weekly training frequency showed a significant, strong positive correlation with Stroop Test scores (rho = 0.529; p 0.001), indicating better inhibitory control among students who trained more frequently. Stroop Test scores were also significantly negatively correlated with TMT completion time (rho = −0.402; p = 0.004), Digit Span scores were significantly negatively correlated with TMT time (rho = −0.290; p = 0.041), and Digit Span scores were significantly positively correlated with Stroop Test scores (rho = 0.315; p = 0.026); in other words, all three executive function measures were significantly intercorrelated. Correlations between training frequency and Digit Span (rho = 0.257; p = 0.072) and TMT (rho = −0.171; p = 0.234) were not statistically significant. Weekly training frequency was selectively associated with inhibitory control, but not consistently with working memory or processing speed/cognitive flexibility, among sport science students. These findings support the hypothesis that the cognitive benefits of physical activity are domain-specific and most consistent for tasks demanding high inhibitory control.